Negative effect of global warming on biological control is mitigated by direct competition between sympatric parasitoids - Cebolla, Ruth; van Baaren, Joan; Tena, Alejandro (Elsevier, 2018)
Parasitoids are among the most important and successful groups of natural enemies used in the biological control of insect pests. In most systems, several parasitoid species can parasitize the same pest. The coexistence of parasitoids in agroecosystems and their efficacy as biological control agents may be disrupted by global warming. An increase of approximately 3 °C is predicted by the end of the twenty-first century in the Mediterranean basin (IPCC, 2014). In this context, we compared the present and future performance of two sympatric parasitoids of the genus Aphytis (Hymenoptera: Aphelinidae), which control the armoured scale Aonidiella aurantii (Hemiptera: Diaspididae) in Mediterranean citrus, either alone or in combination. The net reproductive rate (R0) of the introduced Aphytis melinus DeBach was higher than that of its competitor, the native Aphytis chrysomphali (Mercet), under current conditions. The two parasitoids responded differently to higher temperature and competition. The R0 of A. chrysomphali decreased by 50% when both parasitoids competed in the same patch, but was not affected by the temperature increase. The R0 of A. melinus decreased approximately 46% with the increase in temperature because the proportion of females was reduced. However, the presence of A. chrysomphali competing in the same patch mitigated the negative effect of the increase in temperature on A. melinus (R0 decreased by only 16%). Overall, our results suggest that global warming will have a negative effect on the biological control of A. aurantii and that this effect will be higher in areas, such as southern Spain, where A. melinus has displaced A. chrysomphali.